Technology Education for Sustainable Futures - Pavlova, Margarita (Design and Technology Education: An International Journal, 2006)
The article develops the argument that Technology Education has a particular and important role in achieving sustainable futures within different societies. The starting point for this article is an observation of two boys making toys out of materials that would normally be thrown away. Implicitly these activities contribute towards sustainable futures through utilizing waste and using fewer resources. However, how these activities can be transformed into classroom activities, so they would be the part of education for sustainability learning and contribute more to sustainable development, and how they would be different for different contexts are the questions addressed in this paper. Activity theory, and the model of an activity system, developed by Engestrom (1987) are used to analyse the differences in unstructured and structured activities of the children involved in the creation of toys and the conclusion is made that the differences are related to almost all components of the activity model. Then, the comparison is made between structured activities within different contexts. The conclusion is drawn that the main difference is concerned with the object of activity. The case study of Russia is used to analyse the specificity of a particular context (Nizhny Novgorod region) and to identify the object of activity relevant to technology education classroom within this region. The conclusion is made that a theoretical analysis on the basis of activity theory and a case study approach demonstrate that Education for Sustainability (ES) can be effectively addressed via technology education. However, it is necessary to pay particular attention to the object of students’ activity, so it would be relevant to the particular context.